Draft Annual Plan 1987-88 Maharashtra State Part One - Planning Commission (Planning Commission, 1986)
The Planning Commission has requested the State Government to formulate the Introduction draft plan proposals for the Annual Plan (1987-88) which will be discussed in the working group meeting of the Planning Commission on 15th December 1986.
Government of Maharashtra : Planning Department